SISTEM PEMIDANAAN ANAK SEBAGAI PELAKU TINDAK PIDANA PERSPEKTIF UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Guntarto Widodo (Universitas Pamulang, 2016)
This study describes The principles system of legal protection against Children as criminal perpetrator in Law of the Republic of Indonesia Law Number 11 of 2012 concerning Juvenile Criminal Justice System refer to the Convention on The Rights of The Child and it has covered most of the principles of child protection perpetrator as well. The research method used in this study is a normative legal research because it includes the scope of legal dogmatic learning or researching legal rules. The study also found First, The provision of punishment against the child has been in accordance with that stipulated in Law Number 23 of 2002 concerning Children Protection which states that imprisonment can be applied to the child when there is not last effort any longer, and shall be executed separately from the adult prison;,Second, The Child protection efforts shall be implemented by imposing sentencing restorative (restorative justice) and diversion in the event that completing the requirement of Law Number 11 of 2012 concerning Juvenile Criminal Justice System. Keywords: Sentencing System, Criminal Justice System, Child Protection